ZONING PRONE TO LANDSLIDES THROUGH 3D VISUALIZATION USING GEO CAMERA APPLICATION IN CIKUYA VILLAGE, CULAMEGA DISTRICT, TASIKMALAYA REGENCY - Nur Aisah, Siti; Ari Lesmana, Vinki (Journal of Marine-Earth Science and Technology, 2021)
Cikuya Village Culamega District Tasikmalaya District, West Java, landslide prone areas that cause material losses and fatalities. The landslide occurred because Cikuya Village is located in the South Mountain Zone with hilly morphology so that it has a steep slope. Other characteristics cause landslides due to high rainfall intensity, geological conditions, soil types, and land use that are not in accordance with the carrying capacity of the environment. Prevention efforts that can be done by measuring the characteristics of landslide prone and 3D visualization zoning maps using map overlays to produce zoning maps and land suitability using ArcGis 10.5 software and Geo Camera applications The results of this study show the characteristics that cause landslides are high rainfall intensity ranging from 2,203 - 3,054 mm / year, Steep slopes range from 8° - 40°, geological conditions (types of rocks) are divided into two types, namely sedimentary rocks and volcanic rocks, podsolic yellow red soil types that are not good in water escape, as well as land use that is not in accordance with the conditions and carrying capacity of the region. The results of the analysis of assessment, weighting and overlay zoning of disaster-prone areas are divided into three "non-prone" hazardous landslide zones with an area of 7,597 hectares, a "prone" zone with an area of 1,972,147 hectares, and a "very vulnerable" landslide vulnerability zone with an area of 256,968 hectares. Further analysis is that land suitability is divided into three "appropriate" zones with an area of 1,057,391 Hectares, "somewhat appropriate" with an area of 1,080,373 Hectares, and "incompatible" with an area of 98,948 Hectares. It is expected that the results of this study can be a reference for the community in recognizing landslide-prone zone areas in Cikuya Village, Culamega Subdistrict, Tasikmalaya Regency.